DESIGN AND OPTIMIZATION OF GASTRO RETENTIVE BILAYER FLOATING TABLETS OF LEVODOPA - Veeraganti, Alekhya; Jogala, Satheesh; Damayanthi, Singanaboina; Konda, Sri Chaya Reddy; Atthapu, Thirupathaiah (International Journal of Pharma and Bio Sciences, 2026)
According to this perspective, the gradation of the available medication delivery technologies is the main obstacle faced by healthcare providers. Effective disease/disorder management, fewer side effects, and more patient compliance in an economical way are the ultimate goals of any medication delivery system. By controlling the drug release in the body in a well-defined, regulated manner, the therapeutic indices of the medicine could be maximised while the indices of unfavourable reactions or side effects might be minimised. Parkinsonism diseases are treated with levodopa, an immediate precursor of dopamine. The goal of the current study is to create levodopa floating matrix tablets that will increase the drug’s stomach residence time and improve absorption. The goal of the current study was to create levodopa floating tablets using the direct compression method. For a number of post-compression evaluation criteria, including tablet thickness, hardness, weight variation, floating lag time, total floating time, content homogeneity, and in vitro drug release, the formulated tablets demonstrated satisfactory results. Compared to the other formulations, Formulation F2 provided more regulated drug release and floating characteristics. The Korsmeyer-Peppas model, Higuchi model, and first-order model fit the release pattern of the F2 formulations the best. In conclusion, the proposed levodopa floating matrix tablet may be considered a promising formulation that could provide better management of Parkinsonism disorders by releasing the medication in the stomach at a controlled rate.